Optimization of Athlete Management (Regional Student Sports Training Education Center) to Become a National Athlete Barn in the Youth, Sports, and Tourism Office of Musi Banyuasin - Damanik, Alvian (Journal of Social Work and Science Education, 2023)
Basic Training for Civil Servant Candidates is held to form professional Civil Servants with character, namely civil servants whose character is formed by the attitude of state defense behavior, basic civil servant values, and knowledge of the position and role of civil servants in the Republic of Indonesia, as well as mastering their fields of duty so that they are able to carry out their duties and roles professionally as public servants. The actual issue that I raise is the lack of optimal management of athletes (Regional Student Education and Training Centers) To fulfill the task of administering the government, it is necessary to have reporting from related parties so that the data obtained can be accounted for and in accordance with the expected time. It needs to optimize management. So that currently the Youth, Sports and Tourism Office has not been able to maximally fulfill its duties in organizing government in the field of sports, especially the community sports section. For this reason, the Youth, Sports and Tourism Office through the author considers the need to optimize the management of athletes at the Youth, Sports and Tourism Office to fulfill their duties optimally. Therefore, in order to carry out actualization by applying the basic values of civil servants, the author raises an actualization plan entitled optimizing the management of athletes.